2009
DOI: 10.3109/14767050903019684
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid soluble human leukocyte antigen-G in term and preterm parturition, and intra-amniotic infection/inflammation

Abstract: Objective Circulating soluble HLA-G (sHLA-G) has been associated with pregnancy complications, and determination of sHLA-G concentrations in amniotic fluid (AF) has been reported in normal pregnancies. Our aim was to determine if the AF concentrations of sHLA-G change with advancing gestation, spontaneous labor at term, and in patients with spontaneous preterm labor (PTL) with intact membranes, as well as in those with preterm prelabor rupture of membranes (PROM), in the presence or absence of intraamniotic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 197 publications
(187 reference statements)
2
20
0
Order By: Relevance
“…In a subgroup analysis of our data, spontaneous PTB was associated with increased basal plate HLA-G, whereas indicated PTB was not. Our data are consistent with the findings of Kusanovic et al, who demonstrated that levels of soluble HLA-G in the amniotic fluid were elevated in patients with spontaneous preterm labor[32]. …”
Section: Discussionsupporting
confidence: 93%
“…In a subgroup analysis of our data, spontaneous PTB was associated with increased basal plate HLA-G, whereas indicated PTB was not. Our data are consistent with the findings of Kusanovic et al, who demonstrated that levels of soluble HLA-G in the amniotic fluid were elevated in patients with spontaneous preterm labor[32]. …”
Section: Discussionsupporting
confidence: 93%
“…Thus, this information can be used for counseling patients about their risk for delivery and the need to assess the AF for inflammation. Previous studies have reported that intra-amniotic inflammation is associated with preterm labor[4-7, 12-13, 15, 18-19, 21-24, 27-29, 31-34, 38, 41-43, 47-49] and is a risk factor for adverse outcome [2, 14, 16, 26, 39, 45, 52-53, 56-57]. …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of disease responsible for chronic chorioamnionitis is thought to be maternal antifetal rejection. There is also evidence for antibody-mediated fetal rejection; maternal antibodies against paternal human leukocyte antigens (HLA) have been demonstrated in patients with chronic chorioamnionitis [93, 99, 100, 127]. The control group consisted of uncomplicated term deliveries.…”
Section: Methodsmentioning
confidence: 99%